Detection of Acanthamoeba spp. in groundwater sources in a rural area in the Philippines. (12th January 2023) - Padua, Mark F F E.; Masangkay, Frederick Ramirez; Alejandro, Grecebio Jonathan D.; Milanez, Giovanni De Jesus
Abstract: Research on free-living amoebae (FLA) and its public health implication as an etiologic agent of parasitic infection in humans has recently gained traction in the Philippines. This study aimed to identify potential FLAs in collected groundwater samples from Masinloc, Zambales, Philippines. Fifty-four (54) water samples were collected in 250-mL sterile polyethylene containers by purposive sampling from selected groundwater sources in six (6) barangays of Masinloc. The samples were vacuum filtered through a 1.2-μm pore glass microfiber filter, cultured onto non-nutrient agar (NNA) lawned with Escherichia coli, and observed microscopically for amoebic growth for 14 days using light microscopy. Amoebic growth was observed in 11.1% (6/54) of water samples. DNAs from positive samples were extracted and were made to react with polymerase chain reaction using Acanthamoeba -specific JDP1 (5′-GGCCCAGATCGTTTACCGTGAA-3′) and JDP2 (5′-TCTCACAAGCTGCTAGGGAGTCA-3′) primers, and universal primer Euk A (5′-AACCTGGTTGATCCTGCCAGT-3′) and Euk B (5′-TGATCCTTCTGCAGGTTCACCTAC-3′). The presence of Acanthamoeba genotypes T4, T7, and T11 was confirmed using molecular and phylogenetic analysis. Our results confirmed that groundwater sources from two of six sampling sites (33.3%) in Masinloc, Zambales, were contaminated with potentially pathogenic FLAs. Proper identification of risk factors that may cause contamination consequently leads to the implementation of programs that will prevent future infections. HIGHLIGHTS: First report of Acanthamoeba astronyxis in groundwater sources in the Philippines. First report of Acanthamoeba genotype T4 in groundwater sources in the Philippines. Confirmed pathogenic Acanthamoeba spp. through thermo-tolerance testing in groundwater. First extensive survey of FLAs in groundwater sources in the Philippines. Potential risks of FLA occurrence in groundwater sources.